Phycobilisome Mobility and Its Role in the Regulation of Light Harvesting in Red Algae - Kaňa, Radek (American Society of Plant Biologists, 2014)
Red algae represent an evolutionarily important group that gave rise to the whole red clade of photosynthetic organisms. They contain a unique combination of light-harvesting systems represented by a membrane-bound antenna and by phycobilisomes situated on thylakoid membrane surfaces. So far, very little has been revealed about the mobility of their phycobilisomes and the regulation of their light-harvesting system in general. Therefore, we carried out a detailed analysis of phycobilisome dynamics in several red alga strains and compared these results with the presence (or absence) of photoprotective mechanisms. Our data conclusively prove phycobilisome mobility in two model mesophilic red alga strains, Porphyridium cruentum and Rhodella violacea. In contrast, there was almost no phycobilisome mobility in the thermophilic red alga Cyanidium caldarium that was not caused by a decrease in lipid desaturation in this extremophile. Experimental data attributed this immobility to the strong phycobilisome-photosystem interaction that highly restricted phycobilisome movement. Variations in phycobilisome mobility reflect the different ways in which light-harvesting antennae can be regulated in mesophilic and thermophilic red algae. Fluorescence changes attributed in cyanobacteria to state transitions were observed only in mesophilic P. cruentum with mobile phycobilisomes, and they were absent in the extremophilic C. caldarium with immobile phycobilisomes. We suggest that state transitions have an important regulatory function in mesophilic red algae; however, in thermophilic red algae, this process is replaced by nonphotochemical quenching.